2011
DOI: 10.1159/000322978
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Steroid Receptor Coactivator-1 Was Regulated by Postnatal Development but Not Ovariectomy in the Hippocampus of Rats

Abstract: Female steroids such as estrogens and progestins, through their nuclear receptors, play important roles in regulation of the structure and function of the hippocampus. Steroid receptor coactivator-1 (SRC-1) has been detected in embryonic and/or adult hippocampus of rodents, and SRC-1 null mice showed significantly longer escape latency in the Morris maze test, indicating a role of this coactivator in the regulation of hippocampus function. Whether this is regulated by development and circulating ovary hormones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 90 publications
3
10
1
Order By: Relevance
“…We also found that SRC-1 is regulated by development in both sexes and by orchidectomy [28][29] but not ovariectomy in the hippocampus of rats [29]. Furthermore, orchidectomy and letrozole treatment induced decrease of brain SRC-1 in a similar manner [10,30].…”
Section: Page 4 Of 23supporting
confidence: 64%
See 1 more Smart Citation
“…We also found that SRC-1 is regulated by development in both sexes and by orchidectomy [28][29] but not ovariectomy in the hippocampus of rats [29]. Furthermore, orchidectomy and letrozole treatment induced decrease of brain SRC-1 in a similar manner [10,30].…”
Section: Page 4 Of 23supporting
confidence: 64%
“…The Western blot analysis of SRC-1 and PSD-95 was carried out according to our previous description [28,31]. Proteins of hippocampus of the rats or cultured cells were extracted using a Protein Extract Kit (P0027, Beyotime Biotech; Beijing, China) and the protein concentration was determined using a BCA Assay Kit (P0010, Beyotime Biotech).…”
Section: Western Blotmentioning
confidence: 99%
“…For orchidectomy, the skin of the scrotum of the male adult mice was opened, the epididymis was cut and the testes were removed (Harooni et al,2008). Ovariectomy was carried out according to our previous report (Zhang et al,2011a), a small midline incision (∼1.0 cm) was made in the skin halfway between the middle of the back and the base of the tail, starting at the last rib. The skin was moved to one side, and a small incision was made through the peritoneal lining on each side.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported the expression of SRC‐1 mRNA and/or protein in the hippocampus of mice (Bian et al,2011; Nishihara et al,2003) or rats (Meijer et al,2000; Ogawa et al,2001; Zhang et al,2011a, b). Higher SRC‐1 expression in the male hippocampus was reported under physiological conditions in the rats (Bousios et al,2001) and mice (Bian et al,2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation